The loss of large amplitude pulsations at the end of AGB evolution. Issue Volume 14:Issue S343(2019) (August 2018) - Engels, D.; Etoka, S.; Gérard, E.
Abstract: Since 2013, we are performing with the Nancay Radio Telescope (NRT) a monitoring program of > 100 Galactic disk OH/IR stars, having bright 1612-MHz OH maser emission. The variations of the maser emission are used to probe the underlying stellar variability. We wish to understand how the large-amplitude variations are lost during the AGB – post-AGB transition. The fading out of pulsations with steadily declining amplitudes seems to be a viable process.